Cultivation of Underutilized Fruit Crop Malay Apple (Syzigium malaccense) -A Review - Sethunath, Keerthana; Bhaskar, Jyothi; Rajendra, B. N.; Naidu, Singamaneni Alekya (International Journal of Economic Plants, 2025)
Malay apple is a tropical fruit-bearing tree that thrives well in warm, humid climates. It can be easily recognized by its lovely, glossy leaves and the vivid red or pink coloured fruit, which resembles a small apple or pear in shape. Fruits are suitable for table purpose because of its crisp texture, sweet flavour with feeble delicate flowery scent. It is also suitable for preparing value added products such as squashes, ready to serve drinks, desserts and so on. The trees have a wide canopy that offers good shade and grows up to a height of 12 to 18 meters. The tree bears gorgeous bell-shaped flowers, usually pink or red in colour, that attracts bees and other pollinators. The fruits are abundant in antioxidants, fibre, and vitamin C which supports digestive health and strengthens the immune system. Malay apple cultivation requires well-drained soil, lots of sunshine, and consistent irrigation. It finds an important place in local cuisines and customs and is frequently grown in orchards and backyard gardens in tropical regions. Though Malay apple has got great potential, it still remains underutilized and has not found a place in international markets. So, there is a lot of scope for taking up the commercial cultivation of this fruit crop in regions and countries where warm, humid climates prevail. The ecological, nutritional, and economic significance of Malay apple is emphasized in this review, along with its role in supporting regional food habits with sustainable agriculture.